Espaçamentos e épocas de plantio no desempenho produtivo da rúcula - Freitas, Karidja Kalliany Carlos de (Universidade Federal Rural do Semi-Árido, 2006)
Two experiments were carried out in the vegetable garden of Plant Science Department at Universidade Federal Rural do Semi-Árido (UFERSA), Mossoró-RN, to evaluate the influence of different spacings between and within rows and planting times on rocket yield performance. The first experiment was conducted from June to August of 2005 and the second one from September to October of 2005. The experimental design used was of randomized complete blocks in a 3 x 4 factorial scheme with four replications. The treatments of the factorial consisted of the combination of three between row spacings (20, 25 and 30cm) with four within row spacings (5, 6, 7 and 10cm). The rocket cultivar grown was the Cultivada . Evaluations for plant height, number of leaves per plant, shoot dry mass, and green mass yield were made in the rocket. Economics indicators such as gross and net incomes, rate of return and profit margin were determined. There was a significant interaction between planting times and between row spacings and between planting times and within row spacings on shoot dry mass and green mass yield. On the other hand, it was not observed a significant interaction between within row spacings and between row spacings for any evaluated trait in the regrowth. The best agronomic performances of rocket were observed in the second planting time and in the regrowth, and in the spacings of 25cm x 6cm and 20cm x 5cm, respectively. The highest economic indicators were also observed in the second planting time and in the regrowth, and in the spacings of 25cm x 6cm and 20cm x 5cm, respectively. The rocket green mass yield was about 78% higher in the regrowth as compared with those of the first growing
Effects of different spacings and planting times on rocket yield performance
Keywords: Eruca sativa; Planting arrangement; Yield; Economic indicators; Eruca sativa; Arranjo de plantas; Rendimento; Indicadores econômicos; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA